Cam Jansen and the Valentine baby mystery - Adler, David A.; Natti, Susanna (New York : Viking, 2005)
It$1 (Bs Valentine's Day, and Cam's mother is about to give birth. While in the hospital waiting room, something of great value disappears. Cam starts to investigate the mystery and will need to solve it before her Valentine sibling is born.s
Using her photographic memory Cam Jansen joins Eric in solving the mystery of a Valentine's day robbery in a hospital waiting room.
"Case #25"-- cover.
007-up.
630L
Decoding demand: 76 (high) Semantic demand: 82 (very high) Syntactic demand: 76 (high) Structure demand: 82 (very high)
Accelerated Reader
Accelerated Reader AR
Keywords: Jansen, Cam -- (Fictitious character) -- Juvenile fiction; Jansen, Cam -- (Fictitious character) -- Fiction; Theft -- Juvenile fiction; Medical fiction; Memory -- Juvenile fiction; Stealing -- Fiction; Memory -- Fiction; Mystery and detective stories; Mystery fiction